Wernicke’s encephalopathy complicating hyperemesis gravidarum: a case series - Moukit, Mounir; Belaabas, Soufiane; Rahmoune, Mohammed; Allilou, Ismail; Babahabib, Abdellah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Wernicke’s encephalopathy is an acute neuropsychiatric syndrome due to thiamine deficiency. In most cases, it is associated with alcoholism and malnutrition and rarely can be secondary to hyperemesis gravidarum and arise during the first trimester of pregnancy. The clinical signs are specific to this disorder. However, they are unknown by most clinicians, especially obstetricians, delaying treatment and leading to serious problems including maternal mortality. We report a case series of three patients diagnosed with Wernicke’s encephalopathy during the first trimester based on clinical symptoms and radiological signs in two cases and only on clinical findings in case 2. A high dose of thiamine was started intravenously in all patients and the majority of symptoms resolved. Unfortunately, case 3 died, probably to a delay of diagnosis. Given this severity even with rapid treatment, prevention measures with low doses of thiamine supplementation remain at present the best treatment and should be applied in any patient presenting with hyperemesis gravidarum.